Batu Bersurat Terengganu: Satu Tafsiran Terhadap Pelaksanaan Syariah Islam - Abdul Rahim, Rahimin Affandi; Ismail, Paizah; Abd Majid, Mohd Kamil; Md. Dahlal, Nor Hayati (Jurnal Fiqh, 2010)
The Terengganu inscription can be regarded as the earliest evidence for the Islamization of the Malay Peninsula. So far several studies have been conducted toward its contents which attest the earliest known Malay-Muslim Jawi alphabet in the Malay world. Due to its plain and simple nature, most scholars had facing difficulty in analyzing it content, pertaining to the Malay-Muslim?s perception of Islamic law. Based on such background settings, this article will try to analyze the application of Islamic law in the traditional Malay-Muslim society. It had utilized several methodologies, .i.e. the historical, phenomenology and Islamic jurisprudence. With regard to Ilm Usul al-Fiqh, several Islamic legal theories will be used to further comprehend the Sharia substance in the Terengganu inscription. At the end, the study finds that Terengganu inscription had enclosed Islam as an official religion of the Malay-Muslim state. It also includes Islamic legal elucidations in the field of jinayat, mu?amalat and ibadat. Obviously all of those mentioned field where needed to implementation of Islamic law in the society.